1997
DOI: 10.1097/00000421-199704000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Chemotherapy and Radiotherapy for Squamous Cell Esophageal Carcinoma

Abstract: A Phase II study of sequential chemotherapy with 5-fluorouracil and cisplatin followed by radiotherapy was initiated to see whether the use of two therapies sequentially could have an effect on response rate. Thirteen patients with advanced squamous cell carcinoma of the esophagus were treated with 1,000 mg/m2/day 5-fluorouracil days 1-5 continuously and 100 mg/m2 cisplatin on day 1. An average of four cycles (range, one to nine) were given every 28 days; 11 patients received more than three cycles. The radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Additionally, the 2-year and 5-year survival rates were 36% versus 26% ( P < 0.001) and 10% versus 0% ( P < 0.001) [ 8 ]. Two randomized controlled trials (RCTs) confirmed that CCRT rather than sequential chemoradiotherapy resulted in improved patient survival rate in advanced esophageal cancer [ 9 , 10 ]. Consequently, CCRT is the standard of care for unresectable advanced esophageal carcinoma in the United States and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the 2-year and 5-year survival rates were 36% versus 26% ( P < 0.001) and 10% versus 0% ( P < 0.001) [ 8 ]. Two randomized controlled trials (RCTs) confirmed that CCRT rather than sequential chemoradiotherapy resulted in improved patient survival rate in advanced esophageal cancer [ 9 , 10 ]. Consequently, CCRT is the standard of care for unresectable advanced esophageal carcinoma in the United States and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy alone or its use sequentially with radiotherapy is inadequate, and newer approaches are needed to improve survival. [1] In our sequential arm the 2 year survival was 38.46, which is better than the two trials, may be as we have not given any gap between chemotherapy and radiotherapy and we have used methotrexate instead of 5-Fu, which is very effective in squamous cell carcinoma and combination of Cisplatin and methotrexate may have given good survival rates. Methotrexate being an antifolate has good results in squamous cell carcinoma and its toxicity is different from Cisplatin, which acts by forming cross linkage with DNA, hence a combination of two was used thinking to give better results in squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 72%
“…The median survival is less than 10 months, and less than 10% of patients survive for 5 years. [1] Recent studies have suggested that combined chemotherapy and radiation therapy may result in improved survival. Currently, the standard treatment for inoperable esophageal cancer is concurrent chemotherapy and radiotherapy with results comparable to best surgical series, though head to head comparison is difficult due to lack of randomized study.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with advanced esophageal cancer remains extremely poor 1 , 2 . Consequently, various adjuvant or neoadjuvant therapies have been attempted, but their effects have been insufficient to improve survival for esophageal cancer patients 3 –6 . Identifying the parameters able to select patients likely to benefit from adjuvant or neoadjuvant therapies is very important.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent improvements in surgical techniques and preoperative management for esophageal cancer, the prognosis for patients with advanced esophageal cancer remains poor 1 , 2 . Consequently, multimodal treatments such as preoperative chemotherapy and/or radiotherapy, as well as post‐operative administration of these therapies, have been attempted in addition to surgery 3 –6 . Sensitivity of esophageal cancers to these treatments is variable, and prediction of the effect of these treatments has not been possible.…”
Section: Introductionmentioning
confidence: 99%